Perbedaan Kandungan Zat Gizi Makro dan Mikro pada Tepung Daun Kelor (Moringa Oleifera) Berdasarkan Metode Perlakuan Pendahuluan - Afriza, Renita; Yuska, Definiwita; Ismanilda, Ismanilda (Poltekkes Kemenkes Padang, 2025)
Moringa leaves (Moringa oleifera) are highly nutritious. Processing into flour extends shelf life, facilitates use, but the initial treatment methods affect its nutrient content. This research investigated how different pre-processing treatments (boiling blanching, steaming blanching, and no blanching) impact the macro- and micronutrient profile of Moringa leaf powder. The study was carried out from June to September 2023 using a true experimental design, applying specific pre-treatments before the leaves were dried and ground into powder. The macronutrient composition was assessed using the proximate analysis method, whereas mineral levels were measured by spectrophotometric techniques carried out at the Industrial Research and Standardization Center (BARISTAND) Padang. The results indicated considerable variation in nutritional content based on treatment type. Boiling blanching: carbohydrates 6.24%, protein 51.32%, fat 23.54%, moisture 12.68%, ash 5.11%, iron 55.16 mg/kg, calcium 9715.61 mg/kg, zinc 21.33 mg/kg.Steaming blanching: carbohydrates 16.35%, protein 47.93%, fat 44.29%, moisture 8.56%, ash 6.96%, iron 50.80 mg/kg, calcium 9453.80 mg/kg, zinc 22.70 mg/kg. No blanching: carbohydrates 26.41%, protein 47.40%, fat 48.75%, moisture 9.37%, ash 8.44%, iron 56.64 mg/kg, calcium 14905.11 mg/kg, zinc 26.62 mg/kg. In conclusion, Pre-treatment methods strongly affect the nutritional value of Moringa leaf powder.Therefore,selecting the right method is essential to optimize its use in food processing and community nutrition programs.